Matthew K. answered • 05/04/21

The first step to solving a word problem is to write out what we know in equation form. I will be using Bob's weight is B and Eric's weight is E. In this case, we have 2 unknowns, so we need 2 equations to solve for both values.

From "If Eric weighs less than Bob":

(1) E < B which means B - E > 0 (This will be used for the positive difference)

From "The sum of Eric's and Bob's weights is 9 times the difference of their weights":

(2) B + E = 9 * (B - E)

From "The positive difference of their weights is also 240 pounds less than the sum":

(3) B - E = (B + E) - 240

From (3), we can solve for Eric's weight by cancelling B and rearranging the equation.

(4) -E = E - 240

(5) 240 = 2 * E

(6) E = 120

Now that we have E, we can plug this into (2) to solve for B.

(7) B + 120 = 9 * (B - 120)

(8) B + 120 = 9 * B - 1080

(9) 1200 = 8 * B

(10) B = 1200/8 = 150

Now we have found Bob's weight.

Kaitt L.

Thank you so much for the help!05/05/21